Higher Animal Protein Intake During the Second Trimester of Pregnancy Is Associated With Risk of GDM - Yong, Heng Yaw; Mohd Shariff, Zalilah; Mohd Yusof, Barakatun Nisak; Rejali, Zulida; Tee, Yvonne Yee Siang; Bindels, Jacques; van der Beek, Eline M. (Frontiers in Nutrition, 2021)
Background and Aims The aim of this study was to examine the associations between total protein intake as well as types and sources of proteins with the GDM risk. Method and Results This was a prospective cohort study of pregnant women in Malaysia. Total, animal, and plant protein intakes were assessed using a semi-quantitative food frequency questionnaire. Of the 452 women, 48 (10.62%) were diagnosed with GDM. From pre-pregnancy to the second trimester, most women had 10 – 20 % of energy intake from protein (88.9 – 90.3%) and ≥ 75% of recommended protein intake (74.6 – 86.5%). Women in the highest tertile (T3) of total animal protein intake (AOR= 2.76, 95% CI= 1.27 – 6.04) and red meat protein (AOR= 2.69, 95% CI= 1.27 – 5.70), specifically in the second trimester, had significantly higher GDM risk compared to women in the middle tertile of intake (T2). Interestingly, women in the T3 of egg protein in the second trimester were significantly at lower GDM risk (AOR= 0.43, 95% CI= 0.18 – 0.91) compared to those in T2. Conclusion The highest tertile of animal protein (≥ 42.15 g/day) intake, particularly red meat protein in the second trimester was positively associated with GDM risk, whereas the highest tertile of egg protein was inversely associated with GDM risk. Protein intake before or during early pregnancy was not associated with GDM risk. These findings underscore the importance of sources and types of protein intake, particularly after the first trimester of pregnancy, in relation to GDM risk.